Investigação da infecção pelo Bocavírus Humano em pacientes de diferentes grupos de risco - Caccia, Elaine Regina Baptista [UNIFESP] (2010)
The Human Bocavirus (HBoV) is a recently discovered parvovirus isolate from human respiratory secretions. Published reports pointed to detection rates from 1.3% to 19%. Limited data is available from Southern hemisphere circulation and, particularly in Brazil, there are some reports with a high incidence in children. We investigated samples from children and adults and other risk groups for respiratory diseases with acute respiratory infection. Five hundred thirty four samples collected from seven different risk groups between 2001 and 2008 were investigated for DNA HBoV by in house PCR adapted from Allander (2005). In general, 3% of children (8/264) and 0.4% of adults (1/270) were HBOV positive: 2.4% (3/127) of children from day care, 4.8% (5/103) of children with congenital heart disease, 0.9% of adult bone marrow transplant (1/112), but none of the health care workers (83), adult renal transplantation patients (31) and community patients in the emergency department (44 adults and 34 children). Commonly observed symptoms were runny nose, cough and fever which were usually observed in more than 50% of cases positive for HBoV. The three children with heart disease had mild infection but four co-infected patients with Rhinovirus had dyspnea and wheezing. These data suggest that HBoV infection among adults, including immunocompromised patients is not relevant. Children co-infection is highly observed and this fact highlights the need for better assessment of the HBoV role in the pathogenesis of symptomatic patients.